Paediatric clinical pharmacology in the UK - Choonara, Imti; Sammons, Helen (BMJ, 2014)
Paediatric clinical pharmacology is the scientific study of medicines in children and is a relatively new subspecialty in paediatrics in the UK. Training encompasses both the study of the effectiveness of drugs in children (clinical trials) and aspects of drug toxicity (pharmacovigilance). Ethical issues in relation to clinical trials and also studies of the pharmacokinetics and drug metabolism in children are crucial. Paediatric patients require formulations that young children in particular are able to take. The scientific evidence generated from clinical trials, pharmacokinetic studies and studies of drug toxicity all need to be applied in order to ensure that medicines are used rationally in children.